Impact of OS Patch Management on Cybersecurity Risk Reduction (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
Most of us try to train our body, eat directly, wash our hands and hold our hands healthy - habits that prevent viruses and diseases from going beyond our immune system. A well lap management program works in a similar way. Lapping reduces the number of vectors in the attack that can compromise infrastructure and data, effectively keep the digital environment of an organization healthy. Cyber-attacks in headings are almost daily, and unpublished weaknesses are still a great risk. In 2024, unexpected software was used in about 25% of reported violations. In addition, the use of weaknesses as a vector of primary attacks on time -time increased by more than 180%, revealing the growing press with timely patching.
Keywords: Cybersecurity; OS; Cyber-attacks; viruses; Patch